PROGRAM HIDUP SEHAT UNTUK MASYARAKAT - Sahabudin Sidik (Asian Journal of Innovation and Entrepreneurship, 2013)
Turned out to be a dirty environment is likely to cause various diseases. Some ofthe diseases caused by dirty environment include worms, due to sanitation facilities athome are less suitable to support the spread of worms. Worm eggs contaminating thesoil can be carried away by foot or footwear dirty when entering the house. Worms canbe transmitted if a family does not keep the house and where he lived well, especiallywhen washing hands before eating. Based on observations conducted, there wasinformation that the cleanliness of the houseof Hamlet is still lacking. Residents still lessconcerned about the health of the home. It can be seen from the unequal distribution ofpublic toilets in every house, then by the authors to make this program aimed toinculcate discipline and habit of healthy life for residents Krajan. The program beginswith the collection of citizens and children Krajan after preparing materials-materialsfor counseling. Besides providing dettol and abate as the basic practice of healthy living.After it began the implementation of hand washing and giving abate to the citizens. Theresults achieved in this program is achieving healthy living program in the communitythat will be routinized to become healthy habits, the death of the larva and children inKrajan of participating in the activities of hand washing.